2011
DOI: 10.1002/hep.24547
|View full text |Cite
|
Sign up to set email alerts
|

Conditional disruption of mouse HFE2 gene: Maintenance of systemic iron homeostasis requires hepatic but not skeletal muscle hemojuvelin

Abstract: Mutations of the HFE2 gene are linked to juvenile hemochromatosis, a severe hereditary iron overload disease caused by chronic hyperabsorption of dietary iron. HFE2 encodes hemojuvelin (Hjv), a membrane-associated bone morphogenetic protein (BMP) coreceptor that enhances expression of the liver-derived iron regulatory hormone hepcidin. Hjv is primarily expressed in skeletal muscles and at lower levels in the heart and the liver. Moreover, a soluble Hjv form circulates in plasma and is thought to act as a decoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 46 publications
4
52
0
Order By: Relevance
“…Expression of Hjv in hepatocytes of Hjv-null mice is able to correct the defects of iron metabolism (13). In agreement with this finding, studies in mice with tissue-specific Hjv knockdown demonstrate that hepatocyte-specific expression of Hjv is essential for hepcidin expression, whereas skeletal muscle Hjv is not (14,15).…”
supporting
confidence: 59%
“…Expression of Hjv in hepatocytes of Hjv-null mice is able to correct the defects of iron metabolism (13). In agreement with this finding, studies in mice with tissue-specific Hjv knockdown demonstrate that hepatocyte-specific expression of Hjv is essential for hepcidin expression, whereas skeletal muscle Hjv is not (14,15).…”
supporting
confidence: 59%
“…Loss of HJV causes severe cases of iron loading in humans termed juvenile hemochromatosis (22), and mouse models confirmed that ablation of HJV (23,24), specifically in hepatocytes (25,26), leads to extreme iron overload due to depressed hepatic hepcidin expression. Furthermore, the ligand BMP-6 is essential for appropriate HJV-mediated hepcidin expression (27,28), and serine/threonine type I (predominately ALK3 (29)) and type II (ActRIIA and BMPRII (30)) receptors are required for transmission of this signal.…”
Section: Regulation Of Hepcidin Through the Bone Morphogenetic Proteimentioning
confidence: 93%
“…Soluble HJV has been implicated in suppressing hepcidin expression by acting as a decoy to compete with hepatic HJV for BMP6 (11,27). More recent studies in conditional knockout mice indicated that only the hepatic HJV is necessary for iron homeostasis (38,39). However, these results do not rule out the possibility that soluble HJV acts as a suppressor of hepcidin expression.…”
Section: Control Of Hepcidin Expressionmentioning
confidence: 97%